KESALAHAN PENULISAN KATA DEPAN DI, DAN, KE PADA NOVEL LAYANGAN PUTUS KARYA MOMMY ASF - Sari, Dewi Retno; Fitri, Lili Aulia; Isnaini , Syafina Nur; Wahyuni, Atikah Sri; Siagian, Irwan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Spelling is a guideline needed for writing in the form of scientific, literary, or news writing, so that the work fulfills the elements or procedures for writing using good and correct Indonesian. However, in its application, spelling errors are sometimes found in an essay. This article aims to analyze the errors in writing prepositions in and into the novel Layang Putus by Mommy ASF. The method used in this study is a qualitative descriptive method. Based on the results of the study, the researcher found writing errors in the prepositions at and to. The researcher found 30 errors in writing the preposition at and 12 errors in writing the preposition to. These errors may be caused by the author's lack of understanding in using good and correct spelling. Thus breaking the rules of writing enhanced spelling.